Optical tweezer system with no fluorescent confocal microscope for trapping colloidal nanoparticles - R Nuansri; P Buranasiri; P Limsuwan; H Ou-Yang (My University, 2018)
We describe two optical tweezer systems for the studies of laser trapping of fluorescent colloidal nanoparticles (NPs).The first one, conventional optical tweezer system widely used in laser trapping, requires a fluorescent confocal microscope for observing trapped NPs.The second system, with no microscope, is presented for the first time in this work.The quantity of trapped NPs for this system is estimated from the transmitted laser light intensity that passes through the fluorescent colloidal NPs.Then the transmitted laser light is converted into the voltage signal and measured by an oscilloscope.A small capillary tube to be filled by the colloidal NPs is developed and used in the second system.This tube can be used with light-sensitive cameras for which a danger of damaging by high light intensities exists.Finally, we show that the results obtained using the both tweezer systems are in good agreement.
Keywords: Microfluidic and Bio-sensing Technologies